A longitudinal study on high risk pregnancy and its outcome among antenatal women attending rural primary health centre in Puducherry, South India - Marie Gilbert Majella; Gokul Sarveswaran; Yuvaraj Krishnamoorthy; K Sivaranjini; Kalaiselvy Arikrishnan; S Ganesh Kumar (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Almost 15% of all pregnant women can develop potentially life-threatening complications. As a result, identification of high-risk pregnancy at earliest stage will be useful in directing appropriate intervention. Hence, the current study was done to determine the prevalence and outcome of high-risk pregnancy among antenatal women in rural Puducherry. MATERIALS AND METHODS: A record-based longitudinal study was done during March 2018 among 569 antenatal women who have attended rural health center of tertiary care institute. High-risk pregnancy was classified based on the guidelines from Pradhan Mantri Surakshit Matritva Abhiyan and outcome assessment based on the obstetric and neonatal outcomes. RESULTS: Among 569 antenatal case record reviewed, 315 (55.3%) were in the age group of 20-25 years and majority (463, 81.4%) belonged to below poverty line families; 410 (74.3%) registered their current pregnancy within the first trimester. The prevalence of high-risk pregnancy among study participants was 18.3% (95% confidence interval: 15.3%-21.7%). Majority (81.9%) had term delivery. Regarding obstetric and neonatal outcomes, majority had spontaneous vaginal delivery (73.9%); about 10.4% gave birth to low-birth weight baby, and only 1.7% had stillbirth. Parity, socioeconomic status, and unfavorable outcomes such as low-birth weight, preterm, and postterm delivery were associated with high-risk pregnancy. CONCLUSION: The current study found that almost one-fifth of the pregnant women in rural area have high-risk pregnancy. Unfavorable obstetric and neonatal outcomes were common among high-risk cases. Hence, early detection of high-risk pregnancy needs to be done at primary health-care level to improve the maternal, obstetric, and neonatal outcomes.